ACKNOWLEDGING THE MENTAL LABOR OF NURSES VIA ALERTNESS AND EVALUATION - ‏ Zainab Ali Alghawi, ‏Aisha Marie Alsayed, ‏Shagraa Hassan Ali Sufyani, ‏Faimaa Mohammed Alabsy, ‏Nawal Saeed Alshahrani, ‏Safiah Lbrahim Alfifi, ‏Ahmed Abdullah Alshuwayman, ‏Kholoud Yatei Alkhaybary; Bader Hamad Alhamdani, ‏Misfer Shaaya Aldosari, ‏Ahmed Abdullah Alshuwayman, ‏Fahad Mohammed Alhejaili, ‏Areej Khalil Alajaji, ‏Naemih Marzuq Alhusayni, ‏Manar Mohammed Alruwaili,Ahmed Ibrahim Mohamed Habadi (Chelonian Research Foundation, 2022)
Insufficiently represented in existing vocabulary, the concept of alertness is highlighted in this article as being essential to nursing practice. The authors characterize vigilance as the deliberate observation of patients to detect significant cues and possible problems, drawing on historical and modern sources. Nurses must perform this mental labor in order to guarantee patient safety and encourage healing. To capture the various facets of alertness, the paper suggests two categories of nursing diagnoses: Central diagnoses: Refer to circumstances (such as "ineffective airway clearance") in which nurses are held separately responsible for interventions and results, Surveillance diagnoses: These indicate possible hazards that nurses should keep an eye on and report (such as "risk for hypoglycemia"). The authors contend that nurses can more accurately convey the breadth of their work and how it affects patient care by utilizing both central and surveillance diagnoses in nursing terminology. Keywords: patient safety, professional nursing practice, nursing vigilance, nursing diagnosis .